Impact of Low Public Awareness on BPHTB Payments on the Validity of Land Ownership Certificates in the PTSL Program - Sri Nuryeni (Syntax Idea)
This study analyzes the low public awareness in paying the Land and Building Acquisition Duty (BPHTB) and its implications on land ownership and regional revenue. Various factors such as the lack of education and socialization, misunderstanding of the payment procedures, and cultural and social barriers are identified as the main causes of low public compliance. The impacts of this low awareness include risks to the validity of land certificates, property market value, and legal stability affecting investments. Additionally, this research explores how low BPHTB payments contribute to a decline in local revenue (PAD) and create challenges for regional development. To address these issues, this study recommends more effective outreach programs, simplification of the payment process, and improved collaboration between the government and the community to increase awareness and compliance with tax obligations